The leukocyte receptor complex in chicken is characterized by massive expansion and diversification of immunoglobulin-like Loci. (PLoS Genetics, 2006)
The innate and adaptive immune systems of vertebrates possess complementary, but intertwined functions within immune responses. Receptors of the mammalian innate immune system play an essential role in the detection of infected or transformed cells and are vital for the initiation and regulation of a full adaptive immune response. The genes for several of these receptors are clustered within the leukocyte receptor complex (LRC). The purpose of this study was to carry out a detailed analysis of the chicken (Gallus gallus domesticus) LRC. Bacterial artificial chromosomes containing genes related to mammalian leukocyte immunoglobulin-like receptors were identified in a chicken genomic library and shown to map to a single microchromosome. Sequencing revealed 103 chicken immunoglobulin-like receptor (CHIR) loci (22 inhibitory, 25 activating, 15 bifunctional, and 41 pseudogenes). A very complex splicing pattern was found using transcript analyses and seven hypervariable regions were detected in the external CHIR domains. Phylogenetic and genomic analysis showed that CHIR genes evolved mainly by block duplications from an ancestral inhibitory receptor locus, with transformation into activating receptors occurring more than once. Evolutionary selection pressure has led not only to an exceptional expansion of the CHIR cluster but also to a dramatic diversification of CHIR loci and haplotypes. This indicates that CHIRs have the potential to complement the adaptive immune system in fighting pathogens.